Peran Divisi Bahasa Dalam Meningkatkan Keterampilan Berbicara Bahasa Arab Santri PTQ Imam Ath – Thobari Bogor - Fahruli Baharudin; Moh Abdul Khaliq Hasan (Ukazh : Journal of Arabic Studies, 2026)
This study aims to describe the role of the Language Division in improving the Arabic speaking skills of students at the Imam Ath-Thobari Islamic Boarding School in Bogor. The method used was descriptive qualitative through interviews with the instructor, Language Division administrators, and several students, as well as direct observation of the language program implementation. The results indicate that the Language Division plays a key role in creating bi'ah lughawiyyah through daily activities such as promoting hiwar (religious gatherings), monitoring language use, and administering sanctions and rewards. These programs have proven quite effective in increasing students' courage and fluency in speaking. This effectiveness is supported by the competence of the ustadz (Islamic teachers), the Islamic boarding school culture that emphasizes Arabic, and the commitment of the Language Division administrators. Obstacles include students' lack of awareness of regulations, uneven motivation and discipline, and varying basic Arabic language skills. Overall, the Language Division has made a significant contribution to improving students' speaking skills, although it still requires strengthening aspects of consistency and program optimization.